Ferroptosis-Related Genes in IgA Nephropathy: Screening for Potential Targets of the Mechanism - Wenhui Zhu; Yao Chen; Jing Xiao; Chuchu Cheng; Guijie Ma; Yang Wang; Yonggang Zhang; Ming Chen (International Journal of Genomics)
Conclusions: Our results show that JUN and ATF3 are possibly critical genes in the process of IgAN ferroptosis and may be related with immune cell infiltration.